2006
DOI: 10.1007/s10840-006-9037-1
|View full text |Cite
|
Sign up to set email alerts
|

Focal ablation for atrial fibrillation originating from the inferior vena cava and the posterior left atrium

Abstract: We identified a case of paroxysmal atrial fibrillation (AF) originating from inferior vena cava (IVC) and the low-posterior left atrium (LA). Both foci, the IVC and the low-posterior LA, simultaneously served not only as trigger but also as driver for maintenance of AF. During AF, the IVC and the low-posterior LA continuously demonstrated the rapid and fractionated potentials that exit into both atria with conduction block. Focal ablation for ectopic beats within the IVC and the low-posterior LA completely eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…They demonstrated that the cardiac muscle fibers in the IVC were more plentiful in the anterior aspect than in the posterior aspect. Interestingly, in our case and most of the previous cases (5,6,8,9) in which AF originated in the IVC, The precordial 6 lead rhythm strip shows termination of atrial flutter with a sinus beat (red asterisk), followed by four consecutive ectopic atrial beats at rate 250/min, which showed a narrow positive wave in lead V1 (red arrow). The first conducted beat occurred with the right brunch block, the second was blocked, the third conducted a with a narrow QRS, and the fourth was blocked.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…They demonstrated that the cardiac muscle fibers in the IVC were more plentiful in the anterior aspect than in the posterior aspect. Interestingly, in our case and most of the previous cases (5,6,8,9) in which AF originated in the IVC, The precordial 6 lead rhythm strip shows termination of atrial flutter with a sinus beat (red asterisk), followed by four consecutive ectopic atrial beats at rate 250/min, which showed a narrow positive wave in lead V1 (red arrow). The first conducted beat occurred with the right brunch block, the second was blocked, the third conducted a with a narrow QRS, and the fourth was blocked.…”
Section: Discussionsupporting
confidence: 56%
“…The IVC ablation schemes were not consistent among the past five case reports. In two cases (5,8), focal ablation (like in our case) was chosen; in one case (6), IVC isolation was selected; and in two cases (7,9), radiofrequency was applied in addition to target ablation, consequently achieving IVC isolation. All of the above patients were free of AF during the follow-up without complications.…”
Section: Discussionmentioning
confidence: 99%
“…AF originating from IVC is extremely rare in clinical practice due to the absence of the myocardial sleeve in human IVC (24)(25)(26)(27); nevertheless, we also identified a similar short ERP in the sheep IVC myocardial sleeve. The difference in arrhythmogenesis between the IVC and other thoracic veins is suggested to result from the embryonic developmental process.…”
Section: Discussionsupporting
confidence: 49%
“…The IVC has been reported as a non-PV trigger site in few case reports. 31 Since atrialization of the IVC is limited, triggers from this structure will be rare. Triggers from the IVC presents P-wave morphology and intracardiac activation sequence similar to inferolateral CT ectopies; therefore, direct recording from the IVC is crucial to establish the definitive site of origin.…”
Section: Ivcmentioning
confidence: 99%